Provitamin A carotenoids (PVAC) enriched maize grain, cassava and sweet potato roots: Specification - Ganguli, Tora; Walton, Jenny; Wolfgang Pfeiffer; Boy, Erick; Taleon, Victor; Virk, Parminder; Govindaraj, Mahalingam (BSI Standards Limited, 2022)
HarvestPlus, a division of the International Food Policy Research Institute, has developed a conventional plant breeding process that results in increased levels of minerals and vitamins in seeds and grain. Since this increases the nutritional value of staple foodstuffs, PAS 235:2022 has been produced to help accelerate the adoption of this methodology by setting targets for the levels of vitamin A required for maize, cassava and sweet potato to be designated as “nutrient enriched”.